2002
DOI: 10.1557/proc-740-i12.24
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Attached Functional Inorganic-Organic Hybrid Nano-composite Aerogels

Abstract: ABSTACTNovel materials in which modified inorganic-organic hybrid silica aerogels are attached to polymer chains have been synthesized. The aerogels are based on chitosan, a bioderived polymer from chitin, and they contain silica. The first stage of the modifications includes attachment of isocyanate, amine onto the chitosan chains embedded within the aerogel. These groups are employed in the second stage to develop the reactions required to "string" aerogel particles along functionalized linear polymers or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In terms of chemical functionality, it is a polysaccharide as well as a polyamine. Previous studies have shown the versatile nature of chitosan and the good chemical compatibility with sol–gel based silica materials. , The abundant amino and hydroxyl functional groups on the backbone of chitosan promote the widespread application of the material as effective biosorbents for the removal of dyes, , heavy metals, , and inorganic ions . The presence of polar functional groups (amine and hydroxyl) on the polymer backbone introduce strong dipole moments which favor the interaction with polar molecules (solvent, silica but also other chitosan units) through hydrogen bonding or dipole–dipole interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of chemical functionality, it is a polysaccharide as well as a polyamine. Previous studies have shown the versatile nature of chitosan and the good chemical compatibility with sol–gel based silica materials. , The abundant amino and hydroxyl functional groups on the backbone of chitosan promote the widespread application of the material as effective biosorbents for the removal of dyes, , heavy metals, , and inorganic ions . The presence of polar functional groups (amine and hydroxyl) on the polymer backbone introduce strong dipole moments which favor the interaction with polar molecules (solvent, silica but also other chitosan units) through hydrogen bonding or dipole–dipole interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] A growing body of literature exists in which silica aerogels are combined with organic polymers to produce nanocomposite materials. [11][12][13][14][15][16] While the majority of aerogels described in the literature are silica-based, there are a limited number of references to clay-based aerogels (though in many cases, the authors did not use this nomenclature). The conversion of clay to clay aerogel through freeze-drying results in a rearrangement of clay sheets, creating a lightweight, fabric-like material.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Au-chitosan-silcia aerogels, there are some special chemical possibilities, because the matrix is porous, the chitosan can be functionalized [14,15], and the Au(0) nanoparticles are present. As described briefly in the introduction, this can form the basis for assay, separation and identification methods.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…The synthesis of chitosan-silica aerogels was described in our former work [14,15]. These used in this work are based on a matrix composition, before metal salt addition, that is 10% chitosan and 90% silica by mass.…”
Section: Preparation Of Au(iii)-chitosan-silica Aerogelsmentioning
confidence: 99%